Ruptures in the everyday : views of modern Germany from the ground - Bergerson, Andrew Stuart 1966- HerausgeberIn; Schmieding, Leonard 1978- HerausgeberIn (Spektrum, 2017)
"During the twentieth century, Germans experienced a long series of major and often violent disruptions in their everyday lives. Such chronic instability and precipitous change made it difficult for them to make sense of their lives as coherent stories--and for scholars to reconstruct them in retrospect. Ruptures in the Everyday brings together an international team of twenty-six researchers from across German studies to craft such a narrative. This collectively authored work of integrative scholarship investigates Alltag through the lens of fragmentary anecdotes from everyday life in modern Germany. Across ten intellectually adventurous chapters, this book explores the self, society, families, objects, institutions, policies, violence, and authority in modern Germany neither from a top-down nor bottom-up perspective, but focused squarely on everyday dynamics at work "on the ground.""--Provided by publisher